2020
DOI: 10.5853/jos.2019.02103
|View full text |Cite
|
Sign up to set email alerts
|

Depression after Subarachnoid Hemorrhage: A Systematic Review

Abstract: Background and Purpose Depression is common and debilitating illness accompanying many neurological disorders including non-traumatic subarachnoid hemorrhage (SAH). The aim of this systematic review was to identify and critically appraise all published studies that have reported the frequency, severity and time course of depression after SAH, the factors associated with its development and the impact of depression on patients’ quality of life after SAH.Methods The PubMed database was searched for studies publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 89 publications
(216 reference statements)
4
25
0
Order By: Relevance
“…Although the prevalence of mood disorders after aSAH is high (Al-Khindi et al, 2010 ; Rinkel and Algra, 2011 ; Vetkas et al, 2013 ; Tang et al, 2020 ), few studies have examined the relationship between mood disorders and post-aSAH fatigue. Passier et al ( 2011a ) found higher fatigue scores 1 year after the ictus in patients scoring high on anxiety and depression than in those without such complaints 3 months after aSAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the prevalence of mood disorders after aSAH is high (Al-Khindi et al, 2010 ; Rinkel and Algra, 2011 ; Vetkas et al, 2013 ; Tang et al, 2020 ), few studies have examined the relationship between mood disorders and post-aSAH fatigue. Passier et al ( 2011a ) found higher fatigue scores 1 year after the ictus in patients scoring high on anxiety and depression than in those without such complaints 3 months after aSAH.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the mortality rates are high, survival has improved due to early intervention and advances in management. Remarkably, most aSAH survivors recover without significant neurological deficits, however, even patients with good outcome report substantial problems with fatigue, as well as cognitive and emotional problems (Al-Khindi et al, 2010 ; Nordenmark et al, 2019a ; Nussbaum et al, 2020 ; Tang et al, 2020 ). Fatigue represents the most frequent symptom after aSAH and is found in 50–70% of patients even several years after the hemorrhage (Kutlubaev et al, 2012 ; Western et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety and depression [ 11 , 17 , 18 ] are among the most investigated realms of patient outcome after aSAH with a stable prevalence over the 18-month period after aSAH and an estimated frequency ranging from 27 to 54% and from 5 to 50% in aSAH survivors, respectively [ 9 ]. Likewise, somatoform disorders, especially pain syndromes like cephalgia, are a commonly reported and oftentimes a long-lasting symptom burden after sSAH, plausibly affecting Ghp, poorer performance in several cognitive domains, and reduced hrQoL after sSAH [ 9 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survivors harbor serious risks of neurological dysfunction, functional disability, and cognitive impairment [ 9 , 10 ], even months to years after ictus [ 11 , 12 ]. There is a marked disparity between reattained functional independence in up to 70% [ 13 ] of the sSAH patients and considerable long-term neuropsychological deficits [ 9 , 10 , 14 ] in up to 94.6% [ 15 ] with a reduced health-related quality of life (hrQoL) in 35% of the patients 1 year after sSAH [ 12 , 16 ], anxiety (in up to 54%) [ 11 , 17 ], depression (approaching 61.7%) [ 17 , 18 ], and, in up to two-thirds [ 9 , 19 ], the inability to reassume one’s previous occupation [ 19 , 20 ] [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although brain aneurysms are still a major challenge for neurosurgeons, SAH mortality has decreased by 17% over the past thirty years [17,18]; a similar decrease in mortality of 18-19% is reported by other authors [19,20]. Unfortunately, many people who survive SAH have long-term cognitive deficits and a reduced quality of life [21].…”
Section: Discussionmentioning
confidence: 53%